Innovation of Teaching Strategies in Factors Associated with Flexible Learning of Drafting Students - Flores, Cariza A.; Daran, Danilo N.; Aquino, John Michael D.; Aranilla, Kris Jon Jay F. (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the Study: This study examines the intersection of flexible learning strategies, psychological well-being, and academic success among drafting students, a group that has received limited attention in existing academic literature. The research aims to uncover how flexible learning techniques impact students’ mental health and academic performance, providing insights that inform innovative teacher training programs and instructional approaches tailored to this unique demographic. Methodology: A descriptive research design was employed, using purposive sampling to select participants. Data were collected through survey questionnaires, and statistical analysis was conducted using the Statistical Package for the Social Sciences (SPSS). The study focused on drafting students aged 18 to 23, many of whom come from financially struggling backgrounds. Participants primarily accessed learning materials through mobile devices and laptops using mobile data or Wi-Fi, engaging in both asynchronous and synchronous learning formats. Main Findings: The study found that students in flexible learning environments demonstrated high psychological well-being and strong academic performance. Interestingly, demographic factors, socio-economic status, and device type did not significantly impact academic success. Instead, age and internet connectivity quality played a critical role in student achievement. Novelty/Originality of the Study: This research provides a novel perspective on the relationship between flexible learning and student well-being in technical education, particularly among drafting students. The findings emphasize the need for equitable digital access and highlight the importance of personalized learning models. Future research should explore learning environments, teacher-student interactions, and digital resource accessibility to further enhance student outcomes.